2015
DOI: 10.1007/s11307-015-0911-z
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evaluation of a Bombesin Analogue Labeled with Ga-68 and Co-55/57

Abstract: NOTA-AMBA was labeled in high yields and RCP with Ga-68 and Co-55/57. High tumor uptake in a subcutaneous mouse prostate cancer model was observed. At 24 h, [(55/57)Co]NOTA-AMBA showed better tumor-to-organ ratios than [(68)Ga]NOTA-AMBA at both 1 and 4 h post-injection. Hence, for imaging, [(55)Co]NOTA-AMBA was found to be superior compared to [(68)Ga]NOTA-AMBA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 29 publications
3
35
0
1
Order By: Relevance
“…The presented method separates 55 Co in 400 μL, a volume that can be quickly evaporated even in the original 1.5 mL vial where the separated fractions are collected, which avoids the use of a large vessel (> 10 mL) connected to a roto-evaporator in which a variable loss of radioactivity may be lost in the large surface area of the glassware as it is difficult to re-dissolve all the activity off the walls of the vessel with a small volume (< 1 mL) of diluted HCl acid. Similarly, in the presented separation method of radio-cobalt from bulk iron, the use of the DGA branched extraction resin in the second part of the separation allows for: 1) the almost complete removal of radio-manganese impurities; and 2) a separated radio-cobalt that is concentrated in a small volume (0.4–0.6 mL) and has an effective specific activity with NOTA that is comparable to the highest one that has been reported using a NOTA-conjugated peptide (Dam et al, 2016). However, regarding the radionuclidic purity of 55 Co, the 58 Ni(p,α) route is worse than the 54 Fe(d,n) one due to the unavoidable presence of MBq amounts of 57 Co from 58 Ni(p,pn) 57 Ni→ 57 Co and from the 60 Ni(p,α) reaction on the 0.505% impurity of 60 Ni in the target material.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The presented method separates 55 Co in 400 μL, a volume that can be quickly evaporated even in the original 1.5 mL vial where the separated fractions are collected, which avoids the use of a large vessel (> 10 mL) connected to a roto-evaporator in which a variable loss of radioactivity may be lost in the large surface area of the glassware as it is difficult to re-dissolve all the activity off the walls of the vessel with a small volume (< 1 mL) of diluted HCl acid. Similarly, in the presented separation method of radio-cobalt from bulk iron, the use of the DGA branched extraction resin in the second part of the separation allows for: 1) the almost complete removal of radio-manganese impurities; and 2) a separated radio-cobalt that is concentrated in a small volume (0.4–0.6 mL) and has an effective specific activity with NOTA that is comparable to the highest one that has been reported using a NOTA-conjugated peptide (Dam et al, 2016). However, regarding the radionuclidic purity of 55 Co, the 58 Ni(p,α) route is worse than the 54 Fe(d,n) one due to the unavoidable presence of MBq amounts of 57 Co from 58 Ni(p,pn) 57 Ni→ 57 Co and from the 60 Ni(p,α) reaction on the 0.505% impurity of 60 Ni in the target material.…”
Section: Resultsmentioning
confidence: 99%
“…Cobalt-55 ( t 1/2 = 17.53 h, 76% β + , E max = 1498 keV) is an intermediate-lived positron-emitting radionuclide that is a useful radiotracer for positron emission tomography (PET) (De Reuck et al, 2004, 1999; Jansen et al, 1997a, 1997b, 1994, 1996b, 1995; Korf et al, 1998; Stevens et al, 1999) and particularly useful for labeling proteins due to its favorable complexation with established bifunctional chelators (Dam et al, 2016; Garousi et al, 2017; Mastren et al, 2015; Srivastava et al, 1994; Thisgaard et al, 2011b; Wallberg et al, 2010). Furthermore, when chelated in oxidation state 3+, the formed complex is considered inert (Duckworth et al, 2009; Regoeczi et al, 1995; Wegner and Spatz, 2013) and therefore it is less prone to interact with ligands in blood plasma and non-targeted organs due to trans-chelation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential use of GRPR-binding peptides in the prediction of surgical margin and metastatic lymph nodes was not addressed so far. The conventional imaging techniques used in preclinical studies never revealed a metastatic lymph node and precise surgical margin in live animals161718. But radiolabelled peptides were able to detect metastatic lymph nodes in patients1519.…”
mentioning
confidence: 99%